Evaluation of cystatin C and neutrophil gelatinase‐associated lipocalin as predictors of mortality in patients undergoing percutaneous mitral valve repair (MitraClip). Issue 11 (16th November 2018) - Dörr, Oliver; Walther, Claudia; Liebetrau, Christoph; Keller, Till; Ortlieb, Regine M.; Boeder, Niklas; Bauer, Pascal; Möllmann, Helge; Gaede, Luise; Troidl, Christian; Voss, Sandra; Bauer, Timm; et al.
Abstract : Background: Compromised renal function is a major risk factor that is strongly associated with poor outcome in patients with mitral regurgitation (MR) and heart failure. Cystatin C, a cysteine protease inhibitor, has been used as a specific and sensitive biomarker of renal function. Neutrophil gelatinase‐associated lipocalin (NGAL) is another sensitive biomarker that specifically indicates functional and structural kidney damage. The aim of the present study was to determine the predictive value of serum cystatin C and urinary NGAL as indicators of mortality in patients undergoing percutaneous mitral valve repair (PMVR). Methods: A total of 120 consecutive patients (age: 77.3 years [±11.2]) undergoing PMVR using the MitraClip system were included in this study. Venous blood and urinary samples were collected for biomarker analysis prior to PMVR. Physiological parameters, medication use, safety events, and all‐cause mortality were assessed 12 months after the procedure. Results: Twelve months after PMVR, there was a significant reduction in the severity of MR ( P < 0.001), and an improvement in the New York Heart Association class ( P < 0.01) was documented. Baseline levels of serum cystatin C (nonsurvivors: 2.4 mg/L [interquartile, IQR: 1.7;3.1] vs survivors: 1.7 mg/L [IQR: 1, 3;2.1], P < 0.001) and urinary NGAL (nonsurvivors: 242.0 ng/mL [IQR: 154.5;281.5] vs survivors: 132.0 ng/mL [IQR:107.0;177.3], P < 0.001) were significantly higher in patients who died during the 12‐month follow‐up period. Conclusion: Cystatin C and urinary NGAL were found to be predictors of long‐term mortality in high‐risk patients undergoing PMVR. Thus, cystatin C and NGAL assessment may be helpful in risk stratification in patients undergoing PMVR.